2016
DOI: 10.1016/j.synbio.2016.02.004
|View full text |Cite
|
Sign up to set email alerts
|

Yeast knockout library allows for efficient testing of genomic mutations for cell-free protein synthesis

Abstract: Cell-free protein synthesis (CFPS) systems from crude lysates have benefitted from modifications to their enzyme composition. For example, functionally deleting enzymes in the source strain that are deleterious to CFPS can improve protein synthesis yields. However, making such modifications can take substantial time. As a proof-of-concept to accelerate prototyping capabilities, we assessed the feasibility of using the yeast knockout collection to identify negative effectors in a Saccharomyces cerevisiae CFPS p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 58 publications
0
12
0
Order By: Relevance
“…Finally, we explored the impact of magnesium concentration of CFPS yields, which has been previously shown to be perhaps the most critical component of CFPS reactions ( 23 , 24 , 30 , 45 ). Magnesium is used to balance the charge present from nucleic acid phosphate groups and other anionic species.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, we explored the impact of magnesium concentration of CFPS yields, which has been previously shown to be perhaps the most critical component of CFPS reactions ( 23 , 24 , 30 , 45 ). Magnesium is used to balance the charge present from nucleic acid phosphate groups and other anionic species.…”
Section: Resultsmentioning
confidence: 99%
“…In this study, we described the development and optimization of a P. putida- based CFPS system, and we were able to achieve sfGFP yields of ∼200 µg/ml in 4 h batch reactions. For comparison, although the current yield is lower than that of the E. coli -based CFPS system (>1000 µg/ml), which has been developed over the past 20 years ( 52 ), it is ten times higher than the recently developed S. cerevisiae -based CFPS system (<20 µg/ml) ( 45 ). The high yielding CFPS capacity, together with the heterologous protein expressing capability of P. putida , makes it a valuable addition to the current existing CFPS platforms.…”
Section: Discussionmentioning
confidence: 99%
“…Notably, we found that metabolic rewiring in these strains improves desired productivities in vitro. This reflects previous efforts to engineer strains for CFE to increase protein yields 27 , 57 , 58 and enable specialized applications 60 – 62 through gene knockouts and/or complementation, but the focus here was on reshaping metabolic flux for small molecule synthesis rather than translation. To our knowledge, this is the first report using multiplexed dCas9 modulation to enhance cell-free biosynthesis, using multiple gRNAs that can be implemented and adjusted more rapidly than knocking out enzymes in vivo 63 or selectively removing them in vitro 64 .…”
Section: Discussionmentioning
confidence: 92%
“…In order to improve the life time of the template and the yield of protein for CFPS, many efforts have been taken from the perspective of inhibiting the activity of the nuclease, preparing an extract from genetically modified strains, improving energy regeneration and byproducts recycling, etc. (Caschera and Noireaux, 2014;Fujiwara and Doi, 2016;Schoborg et al, 2016). These efforts, indeed, improved the protein production of CFPS to a certain degree.…”
Section: Introductionmentioning
confidence: 92%